KRASNOFF, Larry, SÁNCHEZ MADRID, Nuria y SATNE, Paula (2018): Kant’s Doctrine of Right in the Twenty-first Century. Cardiff: University of Wales Press. 245 pp. - García Otero, Quique (Daimon Revista Internacional de Filosofia, 2020)
Reseña de: KRASNOFF, Larry, SÁNCHEZ MADRID, Nuria y SATNE, Paula (eds.) (2018): Kant’s Doctrine of Right in the Twenty-first Century. Cardiff: University of Wales Press.